2017
DOI: 10.1111/maps.13012
|View full text |Cite
|
Sign up to set email alerts
|

The Chelyabinsk meteorite: Thermal history and variable shock effects recorded by the 40Ar‐39Ar system

Abstract: We studied three lithologies (light and dark chondritic and impact melt rock) differing in shock stage from the LL5 chondrite Chelyabinsk. Using the 40 Ar-39 Ar dating technique, we identified low-and high-temperature reservoirs within all samples, ascribed to K-bearing oligoclase feldspar and shock-induced jadeite-feldspar glass assemblages in melt veins, respectively. Trapped argon components had variable 40 Ar/ 36 Ar ratios even within lowand high-temperature reservoirs of individual samples. Correcting for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 55 publications
4
19
1
Order By: Relevance
“…In contrast, shocked chondrites release K-derived 39 Ar at much higher temperatures of >1100°C, often as high as 1400°C (Bogard and Hirsch 1980;Kunz et al 1997;Trieloff et al 2018), most likely due to shockinduced phases (shock glass, jadeite, etc.). This increase of the release temperature of K-bearing phases is also observed for the more calcic plagioclase of shergottites (Korochantseva et al 2009), where plagioclase (maskelynite) separates were found to release both Kderived 39 Ar and Ca-derived 37 Ar at 1300-1400°C, indistinguishable from the 37 Ar release from pyroxene.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, shocked chondrites release K-derived 39 Ar at much higher temperatures of >1100°C, often as high as 1400°C (Bogard and Hirsch 1980;Kunz et al 1997;Trieloff et al 2018), most likely due to shockinduced phases (shock glass, jadeite, etc.). This increase of the release temperature of K-bearing phases is also observed for the more calcic plagioclase of shergottites (Korochantseva et al 2009), where plagioclase (maskelynite) separates were found to release both Kderived 39 Ar and Ca-derived 37 Ar at 1300-1400°C, indistinguishable from the 37 Ar release from pyroxene.…”
Section: Resultsmentioning
confidence: 99%
“…Note that also the majority of the Ne and Ar is released at this temperature. High temperature degassing of minerals is obviously the consequence of shock metamorphism (e.g., Trieloff et al 2018). A small release peak of carbon is also observed at this temperature (Fig.…”
Section: Carbon and Nitrogenmentioning
confidence: 89%
See 1 more Smart Citation
“…The extensive troilite melting, however, requires pressures within the shock stage C-S5 (Moreau et al 2019). The "impact melt" lithology appears either as melt pockets or shock veins, dominating fragments of light-colored lithology, or as a more massive body containing floating light-colored and darkcolored clasts (Trieloff et al 2018). Its shock stage corresponds to C-S6 (veins, pockets-dominated material) or C-S7 (massive melt body).…”
Section: Introductionmentioning
confidence: 99%
“…After that, the meteorite body destructed into thousands of small meteorite fragments and was accompanied by the spread of shock waves. The collision explosion was so powerful that the shock wave may twice round the Earth [4,6,7]. The particular attention should be paid to the fact that this meteorite collision led to the great destruction of buildings and injuries to thousands of people by broken glass mostly [7,8].…”
Section: Introductionmentioning
confidence: 99%